ChemInform Abstract: Amines vs. N‐Oxides as Organocatalysts for Acylation, Sulfonylation and Silylation of Alcohols: 1‐Methylimidazole N‐Oxide as an Efficient Catalyst for Silylation of Tertiary Alcohols. Issue 17 (April 2016) - Murray, James I.; Spivey, Alan C.
Abstract: A comparison of the relative catalytic efficiencies of Lewis‐basic amines vs.